The Effect of Humic and Salicylic Acid on Improving Salt Tolerance of Yellow Hot Chili (Capsicum annuum L.) - Tran Thi Hong Van; Huynh Ba Di (JERAMI : Indonesian Journal of Crop Science, 2022)
Salt stress adversely affects the physiological processes of plants, causing negative changes in the morphology and anatomy of cells, tissues and organs. In order to adapt to the increasingly complex situation of saline intrusion, application of exogenous plant growth regulators shows many positive results to improve the crop's tolerance. In order to survey the effects of humic acid and salicylic acid on yellow hot chili (Capsicum annuum L.), the study was experiated in the greenhouse of Kien Giang University. The experiment was arranged in a completely randomized design, including 2 factors: humic acid (with 4 concentrations: 0 ppm, 1,000 ppm, 1,500 ppm and 2,000 ppm) and salicylic acid (with 4 concentrations: 0 mM, 1 mM, 1.5 mM and 2 mM) were treated separately or in combination (including 16 treatments with 3 replicates). The results showed that the yellow hot chili could grow and bear fruit when watered with saline water from 30 days after planting, however, the yield was low. The record indicated that supplying humic acid at 1,500 ppm into the soil and spraying with salicylic acid at 2 mM to the leaves gave the most effective results, increasing 82% of the yield compared with the control.